The PERSON-ORGANIZATION FIT AND PERCEPTION OF JOB CHARACTERISTICS ON ORGANIZATIONAL COMMITMENT, AND THE IMPACT ON PERFORMANCE IN SHARIA ORGANIZATIONS: - - Wibowo, Ugung Dwi Ario; Aryoko, Yudhistira Pradhipta (SENTRI: Jurnal Riset Ilmiah, 2024)
There are 164 sharia public credit bank or BPR Syariah in Indonesia that ideally, their employees have a commitment to sharia organizations. The antecedents such as person-organization fit and perception on characteristics of their work. Meanwhile, it is necessary to understand the influence of person-organization fit and perceptions of job characteristics on organizational commitment, and their impact on performance in sharia organizations. This research using quantitative research, with the subjects of this research were employees of the BPR Syariah in Banyumas Regency. Data collected by scales and the hypothesis tested by path analysis. The conclusions are: person-organization fit and perception on job characteristics have a significant effect on organizational commitment, as well as their impact as mediators on performance in sharia organizations; perception on job characteristics have a significant effect on performance, but the person organization fit variable does not have a significant direct effect on performance. Organizational commitment as a mediator contributes to the influence of person organization fit and perceptions of job characteristics on performance through organizational commitment as a mediator for employees on sharia organizations with a total contribution of 46.7%.